Examining Self-Reported Physical Contact With Minors Among Pedophile Support Forum Users - Holt, Karen M. (International journal of offender therapy and comparative criminology, 2020)
Minimal research has considered the extent to which pedophile social support forum users disclose physical relationships with minors in the course of their posts. As these forums cater to those who express sexual interests in minors, the users may be at higher risk for contact offenses and require unique treatment and supervision. To address this gap in the literature, this study utilized a quantitative analysis of the posts from 806 users from four separate pedophile support forums to identify the correlates of self-disclosed contact with minors. The findings demonstrated that although most users do not disclose physical contact, those who do share several common traits, specifically fantasies of minors, mentions of relationships with minors, and a sexually suggestive username. The implications of this analysis for our understanding of the role of online forums and potential clinical treatment are discussed in detail.